A Note on the State of Judicial Immunity in ANRS: Alarming Instances. - Mengesha, Abenezer Nahome (Bahir Dar University Journal of Law, 2024)
An independent judiciary is an essential element of a democratic state. To guarantee this, the legislature and the executive wings of the government should have a minor impact on the judiciary and the judiciary should be equipped with special provisions allowing it to defend itself from political pressure.1 The concept of judicial immunity, which protects judges and other judicial officials from civil or criminal liability in connection with their official duties, has been recognized as an important tool to assure full-fledged judicial independence. This article aims to examine the state of procedural judicial immunity in the context of Amhara Regional State. In addition to a critical review of applicable legislations and case analysis, the author conducts unstructured interviews with purposively selected judges working in the region. The article concludes that judges in the region lack legal protection to function independently. It, in particular, underlines that fact arbitrary detention of judges by the police has negatively affected judicial independence as well as public confidence in the judiciary. Based on these findings, the article recommends to the concerned organs to assure procedural immunity for judges in the region to ensure the functional independence of the judiciary and the fair administration of justice.